Assessment of Multilingual Collections in Public Libraries: A Case Study of the Toronto Public Library - Ly, Valentina (Evidence Based Library and Information Practice, 2018)
Objective – The Toronto Public Library has been frequently identified as having an exemplary multilingual collection to serve the information needs of the most diverse population in Canada; however, there is no evidence or collection assessment information available in the literature to validate those claims. This research sought to gain an understanding of the current state of their multilingual collection and compare it to the most recent multicultural population demographics.Methods – This was a case study of the Toronto Public Library multilingual collection using data collected from their online public access catalogue in November 2017. Data was collected about all languages available, with English, French, and the 17 most spoken mother tongues explored in more detail. Language results from the Statistics Canada 2016 Census of Population were also collected. Data was used to calculate and compare the English, French, and language collections to the population of reported mother tongues spoken in Toronto.Results – It was found that the Toronto Public Library has items in 307 languages. While the collection comprises many languages, there is far more focus on official language items than any other language compared to the population in terms of number of items and variety of formats. All 17 non-official languages that were studied had fewer items proportionally available in the catalogue than the proportion of speakers with that mother tongue.Conclusion – The high circulation rates of the Toronto Public Library’s multilingual collection indicate that it has had some success in meeting the needs of its community. However, as the largest library system in Canada with a highly regarded multilingual collection and with many resources for collection development, the Toronto Public Library falls short of having a language collection that is proportional to the languages spoken within the community. While it may not be possible to have a multilingual collection that is entirely representative of the community, this study shows that libraries can use census data to monitor population shifts in order to be responsive to the information needs of their changing communities.